Chitosan reduces naturally occurring plant pathogenic fungi and increases nematophagous fungus Purpureocillium in soil under field conditions - Lopez-Nuñez, Raquel; Prieto-Rubio, Jorge; Bautista, Inmaculada; Lidón-Cerezuela, Antonio L.; Valverde-Urrea, Miguel; Lopez-Moya, Federico; Lopez-Llorca, Luis V. (Frontiers in Agronomy, 2025)
Chitosan effects on soil properties were analysed both under laboratory conditions by incubation with constant humidity and temperature and under field conditions in two persimmon field plots with conventional and ecological management. Chitosan was applied in solution or as coacervates. Application of chitosan reduced soil pH, conductivity (CE), and cation exchange capacity (CEC) in pots when applied at field capacity. Chitosan did not affect field soil respiration, which is greatly dependent of soil moisture and temperature. Metabarcoding showed that chitosan significantly modifies the fungal genera composition of ecologically managed field soil. On the contrary, chitosan caused no significant differences in bacterial taxa composition of soil under field conditions. Chitosan coacervates increased naturally occurring nematophagous fungus Purpureocillium (ca. 50-fold) in soil with respect to chitosan solution-treated soil and untreated controls. In addition, chitosan reduced the inoculum of plant pathogenic fungi Alternaria and Fusarium (20% and 50%, respectively) in field soil. Soil microbial network analysis for ITS2+V1–V2 regions revealed that the nematophagous fungus Pochonia promoted network clustering into modules. Furthermore, network analysis for ITS2+V3–V4 regions showed that the nematode trapping-fungus Orbilia and bacteria belonging to Acidimicrobiales and Cytophagales significantly contributed to network clustering in field soil. Our results show that chitosan coacervates increased soil nematophagous microbiota and that both nematode egg parasites and trapping fungi help to structure soil microbiota.